The geopolitics of Turkey-Kurdistan relations cooperation, security dilemmas, and economies - Demir, Mustafa (Lecturer in international relations) (Kurdish societies, politics, and international relations, 2019)
The main objective of this book is to understand the extent and the motives behind the shift in Turkey's foreign policy towards the Kurdistan Regional Government from an alternative globalist perspective by examining a ten-year period of Turkey's foreign policy